Climate-Smart Village Approach in Nepal: Learning from Global, Regional and Local Knowledge - CGIAR Research Program on Climate Change, Agriculture and Food Security (2016)
A three day workshop on Climate-Smart Village (CSV) Approach was organized from 12-14 September in Nepal. Nearly 100 representatives from various CGIAR centers, development partners and CCAFS regions (Latin America, West Africa, East Africa, South Asia, and Southeast Asia) participated. About 50% participants from Nepal were representatives from national and local government, non-governmental organizations, development partners working in Nepal, private sectors organizations and media. The workshop was organized to bring key stakeholders together with leading experts from different parts of the world to support the development of a Climate-Smart Village program for different agro-ecologies of the country. It was focused on exchanging learnings and experiences from other regions/countries that could be relevant for Nepal. A two day field visit to CCAFS-supported CSVs in the Terai region of Nepal (Nawalparasi) was included in the program. The main objectives of the workshop were to:  Demonstrate the Climate-Smart Village approach for scaling out CSA in Nepal.  Foster South-South learning and exchange to support the development of a national program on climate adaptation through the CSV approach in line with the Agriculture Development Strategy of the country.  Sensitize national and international stakeholders about Nepal government’s priorities on Agriculture Development Strategy on climate risk management.